1990
DOI: 10.21273/hortsci.25.12.1573
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Cyanamide Induces Budbreak of Peaches and Nectarines Following Inadequate Chilling

Abstract: Hydrogen cyanamide (Dormex) treatments were applied to 17 insufficiently chilled peach and nectarine cultivars ≈6 weeks after normal budbreak. Treatment effectively induced vegetative budbreak and reduced shoot dieback. The responses to Dormex treatments were linear, with the 2% rate being more effective than the 0 and 1% rates in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 5 publications
4
30
0
Order By: Relevance
“…These measures may include altering orchard management practices and selective planting. For existing orchards, the application of chemicals such as hydrogen cyanamide may effectively break dormancy in insufficiently-chilled peach crops [47], overhead irrigation to encourage evaporative cooling may aid chill accumulation, and orchard management practices such as controlling tree vigor may help to lower the chill needed for successful bud break [48]. For future orchards, site selection with preferential planting in sites with cooler microclimates, such as low-lying cool-air sinks, may provide an opportunity to increase exposure to chilling temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…These measures may include altering orchard management practices and selective planting. For existing orchards, the application of chemicals such as hydrogen cyanamide may effectively break dormancy in insufficiently-chilled peach crops [47], overhead irrigation to encourage evaporative cooling may aid chill accumulation, and orchard management practices such as controlling tree vigor may help to lower the chill needed for successful bud break [48]. For future orchards, site selection with preferential planting in sites with cooler microclimates, such as low-lying cool-air sinks, may provide an opportunity to increase exposure to chilling temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…at concentrations >0.6 M. However, H 2 CN 2 applied at 0.1 to 0.6 M promoted vegetative growth when accumulated chilling hours were <474 CUs. In contrast, Dozier et al (1990) reported that peach and nectarine trees responded linearly to H 2 CN 2 levels applied on 15 Mar. after 650 CUs, with the highest budbreak at the 2% (0.5 M) rate.…”
mentioning
confidence: 87%
“…One characteristic common to most dormancy-breaking treatments is that they are effective only over a narrow range at nearlethal dosages (Erez, 1987;Fuchigami and Nee, 1987). Thus, variable effectiveness in overcoming dormancy and phytotoxicity is commonly encountered (Dozier et al, 1990;Wolak and Couvillon, 1976). Factors that contribute to the variable responses include: time of application (Fuchigami and Nee, 1987;Wolak and Couvillon, 1976), physiological stage of bud development (Fuchigami and Nee, 1987), nutritional status (Terblanche and Strydom, 1973), postapplication temperatures (Erez, 1987) and amount of chilling accumulated (Erez, 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…And while almond, like most Prunus species, exhibits S -RNase based gametophytic self-incompatibility, peach is selfcompatible (Hedrick et al, 1917;Wellington et al, 1929). Almond and peach also differ for other traits, such as life span (Gradziel, 2011), chilling requirements (Alonso et al, 2005;Dozier et al, 1990;Scorza and Okie, 1991), and adventitious root generation (Kester and Sartori, 1966).…”
Section: Introductionmentioning
confidence: 99%